STUDYING THE PREVALENCE OF AUTOIMMUNE THYROID DISEASES IN ADOLESCENTS LIVING IN FERGANA REGION (International journal of artificial intelligence, 2026)
This article analyzes the prevalence of autoimmune thyroid diseases among adolescents living in the Fergana region and examines their clinical and demographic characteristics. The study results highlight subclinical and overt hypothyroidism, age and gender distribution, and the association with regional iodine deficiency. The paper provides evidence for developing regional health strategies and implementing early detection measures.